Chinese Women and the Cyberspace - Kuah-Pearce, Khun Eng (ICAS Publications Series, 2008)
This volume examines how Chinese women negotiate the Internet as a research tool and a strategy for the acquisition of information, as well as for social networking purposes. Offering insight into the complicated creation of a female Chinese cybercommunity, Chinese Women and the Cyberspace discusses the impact of increasingly available Internet technology on the life and lifestyle of Chinese women-examining larger issues of how women become both masters of their electronic domain and the objects of exploitation in a faceless online world. University of Hong Kong. This title is available in the OAPEN Library - http://www.oapen.org.